The study of stemming algorithm for Malay words that start with the letter 'B' from translated Quran documents / Azriana Ahmad - Ahmad, Azriana (1999)
Stemming algorithm have been developed in many different languages. The Malay stemming approach has been named Rules-Application-Order. The performance of this Malay stemming algorithm is tested using translated Quran documents and Malay dictionary. The words that start with the letter 'b' are extracted from the translated Quran documents as test data. Then, using these words in the experiment on the stemming algorithm is tested employing all the possible combination of affixes rules. The percentages of each combination are compared. The main objective of this study is to test the different combination of affixes for words that start with 'b'. Findings such as words that are wrongly spelt in the translated Quran documents are corrected. Other problems that exist are words that could not be stemmed at all using all the combination. The result of this experiment is to help for future work to correct the problems that are detected for the word that starts with the letter 'b'.